Serum antibody and cellular responses in LEW and F344 rats after immunization with Mycoplasma pulmonis antigens. - Simecka, J W (1987)
Mycoplasma pulmonis causes a chronic respiratory disease in rats which is more severe in LEW than in F344 rats. This study compared the ability of each of these rat strains to produce specific immune responses to M. pulmonis antigens. By an enzyme-linked immunosorbent assay, LEW rats were found to produce approximately 10 times lower levels of specific immunoglobulin G (IgG) after immunization with M. pulmonis antigens than F344 rats, while no significant difference was found in the levels of IgM. The difference in IgG levels was due to much greater levels of specific IgG2b (about 50 times) in F344 rats; no differences were found in other subclasses. Nonimmune LEW rats were found to have as much total IgG2b in their sera as unimmunized F344 rats by a single radial immunodiffusion test; thus, the difference was not due to the inability of LEW rats to produce IgG2b. In contrast to the antibody response to M. pulmonis antigens, anti-keyhole limpet hemocyanin IgG responses in LEW and F344 rats were similar, but F344 rats produced significantly more (about 21 times) IgG2b than was found in M. pulmonis responses. Antisera from F344 rats recognized several additional M. pulmonis antigens than antisera from LEW rats; however, this could not explain the differences in the level of IgG2b in LEW and F344 rats. In vitro stimulation of splenic lymphocytes with M. pulmonis antigens from immunized F344 rats produced much greater proliferative responses than in LEW and nonimmune F344 cells. Thus, the susceptible rat strain LEW produced lower cellular and humoral immune responses to M. pulmonis antigens than the resistant rat strain F344 after immunization.